2016
DOI: 10.3233/thc-151117
|View full text |Cite
|
Sign up to set email alerts
|

Internet based personalized feedback interventions for gamblers in Singapore: First results

Abstract: This is one of the first few studies to demonstrate and replicate the potential use of an Internet based intervention for non-problem and problem gamblers. The current study has demonstrated that individuals are generally receptive towards such an intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A similar study was done on gambling in Singapore in which a personalized online feedback survey was developed. Different versions were developed and made available in English and Chinese and demonstrated that the individuals who participated received them well [ 28 ].…”
Section: Reviewmentioning
confidence: 99%
“…A similar study was done on gambling in Singapore in which a personalized online feedback survey was developed. Different versions were developed and made available in English and Chinese and demonstrated that the individuals who participated received them well [ 28 ].…”
Section: Reviewmentioning
confidence: 99%
“…The alcohol tracker application is just one of the two smartphone innovations that the authors wish to highlight that could potentially help individuals who are at-risk. The only smartphone-based intervention for gamblers seemed to be limited to an online gambling self-help workbook currently, which has its theoretical basis on harm reduction and behavioral strategies ( 35 ). Users are asked to identify high-risk situations and provided with personalized feedback with regard to dealing with these situations; and, in addition, they are also able to compute their financial risks ( 35 ).…”
Section: Smartphone Interventions For At-risk Usersmentioning
confidence: 99%
“…The only smartphone-based intervention for gamblers seemed to be limited to an online gambling self-help workbook currently, which has its theoretical basis on harm reduction and behavioral strategies ( 35 ). Users are asked to identify high-risk situations and provided with personalized feedback with regard to dealing with these situations; and, in addition, they are also able to compute their financial risks ( 35 ). In order to help at-risk gamblers, the authors have jointly conceptualized the eGambling Intervention application ( 36 ).…”
Section: Smartphone Interventions For At-risk Usersmentioning
confidence: 99%